Semi virtual workplaces in german financial service enterprises - (:unkn) unknown (IGI Global, 2008)
In this chapter we will present semi virtual workplace (SVWP) concepts in the German financial sector (FS) industry. We give a short introduction into the problem and an overview of the German FS market and its recent developments under European Community (EC) legislation. In the next sections we present three German FS companies that apply successfully semi virtual workplace concepts, followed by detailed descriptions of two semi virtual concepts: strict alternating use of a workplace by two employees (every other day an employee is in his home office) and the concept of the business club, where the employees choose daily their workplace out of a workplace pool when they work on-site. In the last section we compare the concepts and draw conclusion. Further we outline our future research. © 2008, IGI Global.